2014
DOI: 10.1080/1059924x.2014.945712
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Injury Characteristics of Youth Farmworkers in North Carolina: A Pilot Study

Abstract: Agriculture is a unique US industry in how youth are involved. Youth employed in agriculture experience high rates of injury, and youth migrant and seasonal farmworkers may be extremely vulnerable. The primary aim for this analysis is to describe the personal characteristics, work characteristics, occupational safety behaviors, and occupational injuries of North Carolina youth farmworkers. This pilot study uses data from interviewer-administered questionnaires with 87 youth farmworkers. Participants included m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 34 publications
1
40
1
1
Order By: Relevance
“…A few studies present information on occupational injuries experienced by child farmworkers. A pilot study of child farmworkers in North Carolina conducted in 2013 [12] found greater percentages of participants reporting any traumatic injury (60.9% versus 26.2% in the current study), any musculoskeletal injury (54.0% versus 42.6%), and any dermatological injury (72.4% versus 44.1%) than reported for the current study. Both studies found that few of the injured child farmworkers received medical care or missed school or work due to their occupational injuries.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…A few studies present information on occupational injuries experienced by child farmworkers. A pilot study of child farmworkers in North Carolina conducted in 2013 [12] found greater percentages of participants reporting any traumatic injury (60.9% versus 26.2% in the current study), any musculoskeletal injury (54.0% versus 42.6%), and any dermatological injury (72.4% versus 44.1%) than reported for the current study. Both studies found that few of the injured child farmworkers received medical care or missed school or work due to their occupational injuries.…”
Section: Discussioncontrasting
confidence: 66%
“…The interview questionnaire included items taken from existing questionnaires and scales [12,25], with additional items developed by the investigators. The questionnaire was first developed in English.…”
Section: Data Collectionmentioning
confidence: 99%
“…In addition, 24 articles (22%) discussed acculturation, mostly in terms of health and safety risks and responses. While some described acculturation issues among immigrant or migrant workers as context, others discussed it as a determinant of the work performed, hazards or stressors to which workers are exposed, or as a cause or contributing factor to poor physical and mental health . For example, Quandt et al wrote, in the context of their study on skin disease among Latino immigrant manual workers:
“In a subsample of this study sample who received a clinical skin evaluation, indigenous language was associated with a greater overall level of skin disease, including both infectious and inflammatory conditions [Pichardo‐Geisinger et al, 2013].
…”
Section: Resultsmentioning
confidence: 99%
“…Policy briefs have addressed pesticide exposure for farmworkers, an issue with which the US Environmental Protection Agency has been involved over the past decade in developing revised safety standards, the Worker Protection Standard (http://www.epa.gov/pesticide-worker-safety/revisions-worker-protection-standard); housing regulations for migrant farmworkers, the focus of a national discussion concerning housing quality and enforcement of federal and state standards; 21 and child labor, for which current regulations allow exceptions to child labor laws that apply only to agriculture and allow children as young as 10 years old to work for hire in one of the nation’s most hazardous industries. 22–26 Other policy briefs have addressed specific health services concerns, including farmworker access to insurance through the Affordable Care Act, and alcohol consumption and dependence. Generally, the authors of the published papers, along with community representatives and advocates (often those collaborating in the CBPR), have expertise in the policy issue being addressed; if needed, individuals with the additional expertise would be contacted.…”
Section: Lessons Learnedmentioning
confidence: 99%